Deciphering the origins of molecular toxicity of combretastatin A4 and its glycoconjugates: interactions with major drug transporters and their safety profiles in vitro and in vivo. Issue 7 (5th July 2017) - Huang, Zhenhua; Li, Gentao; Wang, Xue; Xu, Hu; Zhang, Youcai; Gao, Qingzhi
Abstract : This study focuses on drug safety and transport mechanisms of CA4 and their glycoconjugates, and aims to engage a new strategy in safer drug design. Abstract : Cellular uptake and transport mechanisms directly correlate with the drug-like profiles of lead compounds. To decipher the molecular origin of the toxicity of combretastatin A4 (CA4), an important microtubule targeting agent, we investigated the interactions between CA4 and six key drug transporters, namely hOAT1, hOAT3, hOCT1, hOCT2, hOATP1B3, and hOATP2B1. Three combretastatin-based glycoconjugates, namelyGlu-CA4, Man-CA4, andGal-CA4 with glucose, mannose, and galactose respectively, were synthesized and their in vitro and in vivo biological characteristics were evaluated. CA4 exhibited significant inhibition against hOAT3 and hOATP2B1, moderate inhibition of hOAT1 and hOCT2, and weak inhibitory effects on hOCT1 and hOATP1B3. Compared to CA4, the inhibitory activities ofGlu-CA4 on the six transporters were minimal. The glycoconjugates were found to have a superior safety profile with their maximum tolerated dose (MTD) values exhibiting a 16–34-fold increase compared to CA4. Given the drawbacks of CA4, the enhanced solubility and safety profiles of CA4 glycoconjugates augur well for further investigation into these intriguing candidates' in vivo efficacy.